Buckling analysis of composite laminates with a circular hole. (November 2020) - Zhang, Cong; Bai, Ruixiang; Lei, Zhenkun; Sun, Zhenya; Su, Kang
Abstract: The stress concentration will appear at the edge of the hole of composite laminate after the openings, which will affect the buckling load and bearing capacity of the composite laminate. Generally, a local reinforcement near the hole is an effective method to alleviate the concentration near the hole and improve the bearing capacity of the structure. In addition, the curvilinear fiber laying scheme is tried to solve the stress concentration problem in this paper. Therefore, the finite element models of ordinary composite laminates with a circular opening, variable angle composite laminates with an open-hole and composite laminates with reinforcement near the circular hole were established by ABAQUS software, the buckling analysis and progressive damage analysis of the above models under shear load were carried out considering the Hashin damage failure criterion and Camanho stiffness degradation criterion. By comparing the buckling load and ultimate load of three different kinds of composite laminates with a circular hole, it is found that besides composite laminates with reinforcement near the circular hole, the curvilinear laying laminates can also increase the stiffness of the laminates and improve the buckling load and ultimate bearing capacity of the structure.